Circadian typology is related to resilience and optimism in healthy adults - Antúnez-Vílchez, Juan Manuel; Navarro-Humanes, José Francisco; Adan, Ana (Taylor and Francis, 2015)
The relationships between circadian typology and several aspects related to mental health, such as satisfaction with life, emotional intelligence, perceived well-being and psychopathological symptomatology have been documented. However, their relationships with two psychological strengths such as resilience and optimism have not been examined yet. Therefore, the purpose of the present study was to explore whether circadian typology is related to both measures, taking into consideration the possible influence of sex. A sample of 1922 participants (978 men), aged between 18 and 60 yrs (30.08 ± 10.53) completed the reduced Morningness-Eveningness Questionnaire (rMEQ), the 10-item Connor-Davidson Resilience Scale (10-item CD-RISC) and the Life Orientation Test-Revised (LOT-R). Circadian typology was associated with different values in resilience (F(2,1915) = 45.89; p < 0.001; [Formula: see text]( )= 0.046) and optimism (F(2,1915) = 37.74; p < 0.001; [Formula: see text]( )= 0.038), independently of the sex. Morning-type subjects showed the highest resilience and optimism scores while the lowest scores were shown by evening-type, exhibiting the neither-type subjects intermediate scores (p < 0.007, in all cases). These results suggest that evening-type subjects could display less capacity to face adversity and adapt positively, as well as less expectance of the occurrence of positive events compared to neither and morning-type individuals. In addition, these results provide new evidence that might improve our understanding about the relationships between circadian typology and psychological traits and disorders. Although future studies with longitudinal designs are needed, the obtained results emphasize that the evening-type could be a risk factor for the development of psychological problems and mental disorders, whereas the morning-type could be considered as a protective factor.
Keywords: Ritmos circadianos; Circadian typology; mental health; morningness-eveningness; optimism; psychological strengths; resilience